Correlation, regression and path-coefficient analysis of physiological parameters associated with berry ripening in grape (Vitis vinifera) - Giridharan, M P; Jindal, P C (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1990-93 to study genetic variability, correlation and direct and indirect effects of physiological parameters associated with crop duration in 15 genetically diverse genotypes of grape (Vitis vinifera L.). The genotypes showed significant difference for total duration of crop (from pruning to berry ripening), leaf area, leaf-area duration, shoot length, number of leaves at 75 days after pruning, leaf-expansion rate, chlorophyll content and stomatal density. It indicated that the magnitude of variability for all the parameters was very high. Shoot length at 75 days after pruning and leaf-area duration were found the most important physiological characters, contributing to the variation in duration of crop growth. Heritability and genetic advance were high for shoot length at 75 days after pruning.